What happens during university lecture Introductions? A case study at a Malaysian University - Ting, Su Hie; Yeo, Jacinta Jiin-Yih (2010)
This study examined teaching and learning practices in lecture introduction in an institution of higher learning, with a particular focus on the content of lecture introductions. A case study was conducted at a Malaysian university, involving lecturers from seven faculties. Forty-seven lecture introductions were audio-taped, transcribed and analysed based on the framework of lecture introductions proposed by Schuck (1970) and Davies (1981). The results revealed that there were four main components of lecture introduction, namely, activating students' prior knowledge, stating aims and objective of the lecture; pointing out importance of mastering the knowledge ; and making announcements and giving instructions. Activating students' prior knowledge emerged as the main purpose of the lecture introductions. To engage students in a communicative discussion, the lecturers made use of questions and both first- and second-person pronouns. However, as the students were generally passive in their responses, the lecturers were found to take control over the speech event throughout the lecture introduction. This study offered insights on the importance of lecturers paying attention to the non-interactive elements and presentation styles to ensure a substantial impact on the learning process.